The lecturer's evaluation form : a critical response by students and lecturers / Julina Munchar ... [et al.] - Munchar, Julina; Ang, Paul Ban Hock; Choy, Tuck Onn; Fung, Anna (Academy of Language Studies & UPENA, 2005)
This study investigates the effectiveness of using the Lecturer's Evaluation Form (LEF) to evaluate lecturers at the Academy of Language Studies (APB) in Universiti Teknologi MARA (UiTM). Questionnaires were given out to students from various faculties in UiTM as well as lecturers teaching in APB, UiTM. The questions were constructed to elicit responses to students' ability in evaluating their lecturers fairly, the effectiveness of the LEF as well as the appropriateness of the criteria stated in the LEF. In general, the lecturers and the students were of the opinion that the students were capable of evaluating the lecturers fairly and that the LEF was an appropriate means of appraising lecturers. However, some suggestions were made on modifying the LEF. The respondents suggested that for the LEF to serve as a useful instrument in determining the lecturer's performance, it needed to be modified and its manner of administration reworked.